Precision and Recall Ratios in Evaluating The Quality of Literature Searches - Nazlı Alkan (Türk Kütüphaneciliği)
Critera by which literature search services may be evaluated, are quality, time and cost criteria. Evaluation judgements are far from being reliable, if not based on these criteria. Relevance, which is the most important quality criteria, is discussed briefly. Precision and Recall ratios, which reflect the numerical value and measure of Relevance, are discussed in some detail. These two criteria frequently used to judge the performance of searches. Significance of Precision and Recall is described and definitions are given. It is considered that these two ratios are the most important performance criteria among all, for they measure Relevance, and Relevance is the most significant component in search effectiveness. For this reason, the present study is limited mainly to the topics of Precision and Recall. However, the text includes some brief description of other criteria as well. In the present study, it is stated as a conclusion that Precision and Recall ratios should be used as Relevancy criteria in judging the performance of literature searches, otherwise all the quality judgements on searches will be false and unreliable.